Beyond the Zero-Sum Game: A Paradigm Shift from Hydro-Politics to Hydro-Economics in the Eastern Nile Basin - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
The Nile Basin remains one of Africa's most contested transboundary water systems, characterized by downstream hydro-hegemony rooted in colonial-era agreements (1929 and 1959) that allocated nearly all flows to Egypt and Sudan while excluding upstream rights. The Grand Ethiopian Renaissance Dam (GERD), Ethiopia's flagship hydropower project, has intensified tensions by challenging historic claims and introducing perceived zero-sum risks to downstream water security. This study examines the paradigm shift from a zero-sum hydro-political framework, focused on fixed volumetric allocations and securitized narratives, to a hydro-economic approach emphasizing system optimization, benefit-sharing, and positive-sum outcomes. Drawing on hydrological modeling, economic valuation, and institutional analysis, the research evaluates coordinated GERD–Aswan High Dam operations, water-energy swap mechanisms, drought and filling protocols, joint augmentation projects, and trilateral institutional architecture under African Union mediation. Novelty lies in reframing the GERD as a regional asset rather than a threat: upstream regulation reduces evaporation losses, attenuates floods, buffers droughts, traps sediment, and anchors clean energy exports via regional grids. Coordinated scenarios yield basin-wide gains, minimized downstream deficits, enhanced hydropower efficiency (up to 35% increase), expanded irrigation, and annual economic benefits exceeding 3 billion, transforming interdependence into mutual prosperity. Findings demonstrate that equitable cooperation outperforms unilateralism, with adaptive protocols and trust-building mechanisms (real-time data sharing, joint modeling, dispute prevention) enabling resilience amid climate variability. The Nile can serve as a model for pan-African transboundary governance, aligning with Agenda 2063 and the Silencing the Guns initiative. In conclusion, the choice is not between Ethiopian development and Egyptian security, but between perpetuating conflict and embracing shared prosperity. Recommendations include establishing a Joint Nile Commission, formalizing water-energy swaps, adopting trigger-based protocols, pursuing joint infrastructure, and leveraging AU guarantees for implementation.